Effect of Contextual Information Literacy Programme on Rural Farmers Awareness, Access and Utilisation of Cassava Farming Inputs in Nigeria - Uzuegbu, C. P.; Igwe, K. N. (MiddleBelt Journal of Library and Information Science, 2020)
Noting the dearth of literature on manifestation of information literacy in rural milieus despite the increasing positive influence of the practice in several endeavours, this paper set out to assess the effect of contextualised information literacy programme on rural farmers’ awareness, access to and utilisation of cassava farming inputs in Nigeria. Guided by two null hypotheses, the field experimental design was adopted, with two villages in Nigeria selected to serve as treatment and control groups on the basis of their homogeneity. The population of the study comprised of all the cassava farming households in both villages, with each cassava farming household considered as a respondent and represented by any member of the household capable of receiving and giving information. A structured interview schedule was used to collect data from the respondents in three batches – the baseline, the first round (first year), and the second round (second year) – using a house-to-house visitation method. The Pearson correlation coefficient test, at a significant level of 0.05, was conducted on the data for the test of the hypotheses. The tests showed that information literacy (in the treatment village) had a statistically significant positive effect on cassava farmers’ awareness, access to and utilisation of cassava farming information and inputs. This was contrary to the effect created by the existing information communication systems in the control village, which statistically impacted only on farmers’ awareness. Thus, unlike existing information communication channels that basically spur peoples’ awareness to information, the practice of information literacy not only acquainted the rural cassava farmers of their information environment but enabled them to access and utilise farming-related information effectively and profitably. The paper recommends that librarians, especially in the public library sector, should practice the theories of information searching, content repacking and selective dissemination of information at the instance of rural famers, using comprehensible formats that take cognizance of rural dwellers’ level of formal education and language of communication.